Unlocking Renewable Energy Potential: The Nexus Between Financial Inclusion and Renewable Energy in Indonesia - Primasrani, Byun Jiye; Parina, Okta (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
Indonesia has pledged to achieve net-zero emissions in 2060. The energy transition can be achieved through financial inclusion. Based on the Environmental Kuznets Curve (EKC) theory, financial inclusion can be a catalyst in reducing environmental impacts if a country has reached the EKC turning point. This study investigates the impact of financial inclusion on the consumption of renewable energy in Indonesia. The data used in this study will be the percentage of renewable energy consumption and the financial inclusion index from the International Monetary Fund 2004 to 2021. Additionally, economic growth and the number of internet users are included as control variables. This study utilizes the Error Correction Model and finds that financial inclusion and internet usage have a negative significant effect on the percentage of renewable energy consumption in the long run. Based on these findings, it can be concluded that according to EKC theory, Indonesia is still in an early stage of development, where increasing financial inclusion and technology still have a negative impact on the environment. Policymakers are encouraged to develop targeted financial inclusion strategies to enhance environmental sustainability. Green finance and green investment are critical solutions to support Indonesia's energy transition.